LEARNING STRATEGIES OF SUCCESSFUL EFL LEARNERS(A case study at one of the most qualified schools in Cimahi) - Restri Martiana, - (2011)
The aim of the study was to discover learning strategies of successful EFL learners at SMKN 1 Cimahi after considering the urgency of learning strategies in EFL learning and teaching. A case study was employed to describe learning strategies used in classroom, learning strategies used outside classroom, other learning strategies, the most useful learning strategies, and the way the most useful strategies were used. Questionnaire and interview were employed to collect the data concerning those matters. The data from the questionnaire were analyzed quantitatively and the data from the interview were analyzed qualitatively by reading the transcription, coding, and sense making. From this study it was discovered that most successful EFL learners in the study had the same characteristics as mentioned by previous researchers in the field. Another conclusion is that most successful EFL learners obtained advantages from strategies that involved their audio and visual devices and gave them plenty of input.